Multimedia Development for Learning Materials for Jepin Gresik Pantai Dance for Junior High School Students - Agisna Niswatana; Aunurrahman; Usman Radiana; Indri Astuti (Institute of Computer Science (IOCS), 2022)
This study uses the ADDIE Robert Maribe Branch paradigm. This research develops Flash CS multimedia. Followed by 42 students of SMP N 18 North Pontianak even semester 2021/2022. Pre-study to the stage, students participate. Pre and post tests, interviews, validation questionnaires, observations, and documentation were used in this study. Qualitative and quantitative data. The average assessment of media experts is 4.45 with 89% in the